2006
DOI: 10.1038/sj.sc.3101891
|View full text |Cite
|
Sign up to set email alerts
|

Effect of postinjury intravenous or intrathecal methylprednisolone on spinal cord excitatory amino-acid release, nitric oxide generation, PGE2 synthesis, and myeloperoxidase content in a pig model of acute spinal cord injury

Abstract: Objectives: To determine whether postinjury methylprednisolone could reduce the generation of known mediators of secondary neurological injury. Methods: Intrathecal microdialysis probes were used to sample cerebrospinal fluid (CSF) for measurement of PGE 2 , glutamate, and citrulline (a byproduct of nitric oxide generation), before and after spinal cord injury in anesthetized pigs. The spinal cord was removed at the end of the study for measurement of myeloperoxidase and methylprednisolone concentrations. Anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 52 publications
2
11
0
Order By: Relevance
“…Compared to systemic administration, i.t. MP administration resulted in a 30‐fold increase in MP concentration in the spinal cord and a greater than 300‐fold increase in the therapeutic index of MP . The present results clearly indicate that central administration of MP and G‐CSF improved the SCI‐induced neurological dysfunctions in rats.…”
Section: Discussionsupporting
confidence: 61%
“…Compared to systemic administration, i.t. MP administration resulted in a 30‐fold increase in MP concentration in the spinal cord and a greater than 300‐fold increase in the therapeutic index of MP . The present results clearly indicate that central administration of MP and G‐CSF improved the SCI‐induced neurological dysfunctions in rats.…”
Section: Discussionsupporting
confidence: 61%
“…Pigs are well established as pediatric and adult models of traumatic brain injury, 28 chronic spinal cord pathology, 12,21,78 and ischemic SCI. 66 Traumatic SCI pig models have used weightdrop, 9 pneumatic impactor, 52 and clip compression 79,92 techniques. In our opinion, pigs are a suitable SCI model because their CNS is similar to that of humans in several respects, including blood supply and flow characteristics, 30,80 white and gray matter distribution, brain and spinal cord growth and development, 22 and spinal skeletal similarities.…”
Section: Injury Modelmentioning
confidence: 99%
“…In addition, recent reports have indicated that Pglycoprotein (MDR1)-mediated exclusion of MP from the spinal cord (14,15) and that MDR1 is capable of interfering with the absorption of MP in the rat small intestine (16). Poor response to the MP therapy was therefore, proposed to be possibly due to incomplete absorption of the MP by overexpression of MDR1 in the GI tract.…”
Section: Introductionmentioning
confidence: 96%